Pengaruh pengalaman microteaching, pengenalan lapangan persekolahan, dan efikasi diri terhadap kesiapan menjadi guru profesional - Amelia Wanda Dhabitah; Dewi Kusuma Wardani (Universitas Negeri Surabaya, 2026)
This research was motivated by the low level of preparedness of some education students to become teachers, despite having taken education courses. This study aimed to analyze the influence of microteaching experience, familiarity with the school environment, and self-efficacy on the readiness to become professional teachers among Economics Education students from the Faculty of Teacher Training and Education at Sebelas Maret University in the 2019-2020 intake. The study used a quantitative approach with proportionate random sampling, resulting in 118 respondents. Data were collected using a Likert-scale questionnaire that met validity and reliability tests, and then analyzed using multiple linear regression. The results showed that microteaching experience, familiarity with the school environment, and self-efficacy each had a positive and significant effect on readiness to become professional teachers. Simultaneously, all three variables made significant contributions to explaining student readiness, with self-efficacy as the most dominant predictor. These findings confirm that the professional readiness of prospective teachers is not only shaped by practical academic experience but also by strengthening self-confidence as an internal psychological factor.